Optimalisasi Kader Pemberdayaan Manusia Untuk Pencegahan Stunting - Rini Harianti; Rika Mianna; Nofri Hasrianto; Rizki Natia Wiji (Universitas Serang Raya, 2023)
The stunting prevalence rate decreased in Kampar Regency from 2017 by 23% of the number of children under five in Kampar until 2019, it was able to be reduced to 11.88% which exceeded the national target of 14%, but the downward trend must still be monitored. Rimbo Panjang Village has a human empowerment cadre (KPM) which has been formed for approximately 1 year and is part of the village cadre that has special duties related to the stunting prevention convergence program. The work pattern of KPM has not been implemented optimally, especially in terms of targets and monitoring of health and nutrition services. Community service activities aim to optimize the role of KPM for stunting prevention in Rimbo Panjang Village. The activity was conducted from April until May 2021 and was attended by 14 cadres. The activity is divided into several stages, namely (1) the preparation, (2) the implementation, (3) the reflection, and (4) the evaluation. The implementation method is conducted through counseling, training or practice, and simulation. The result of this PKM activity is the transfer of knowledge through the various methods presented. It is hoped that in the future, by increasing the knowledge and skills of cadres, it can be implemented in the activities of Posyandu for toddlers so that they can participate in preventing stunting. This activity can be continued regarding training on an e-ppgbm application which is an electronic-based community-based nutrition recording and reporting.